Chronicles in Stone Preservation, Patriotism, and Identity in Northwest Russia - Donovan, Victoria 1981- (NIU Series in Slavic, East European, and Eurasian Studies, 2019)
Chronicles in Stone is a study of the powerful and pervasive myth of the Russian Northwest, its role in forming Soviet and Russian identities, and its impact on local communities. Combining detailed archival research, participant observation and oral history work, it explores the transformation of three northwestern Russian towns from provincial backwaters into the symbolic homelands of the Soviet and Russian nations.The book's central argument is that the Soviet state exploited the cultural heritage of the Northwest to craft patriotic narratives of the people's genius, heroism and strength that could bind the nation together after 1945. Through sustained engagement with local voices, it reveals the ways these narratives were internalized, revised, and resisted by the communities living in the region.Donovan provides an alternative lens through which to view the rise of Russian patriotic consciousness in the twentieth and twenty-first centuries, adding a valuable regional dimension to our knowledge of Russian nation building and identity politics